The relationship between developing talent towards performance management and job satisfaction in selected public universities - Lukman@Zawawi, Mohamad; Kamal, M.Y. (2017)
In a couple of years back, Ministry of Higher Education (MOHE) has understood the vital of Talent Management (TM) in the college framework. MOHE has taken this activity in the wake of seeing the outcome appeared from worldwide universities in the wake of executing TM in their framework. In this way, as a major aspect of TM works on, Developing Talent (DT) is basic so as to furnish staff with aptitudes and hypothesis that matches the mission and vision of the association. Thus, MOHE has thought of a couple of methodologies to execute DT in Malaysia Education Blueprint 2015-2015. On the other part, DT additionally can enhance Job Satisfaction (JS) and Performance Management (PM) of the organizations. Keeping in mind the end goal to inspect the association between this two factors, inquire about has been directed in light of the target of to distinguish the connection amongst DT towards JS and PM in selected public universities in Malaysia. The quantitative strategy has been utilized as a part of a request to gather essential information from 238 respondents in selected public universities in Malaysia. Data acquired from this technique has been examined utilizing IBM Statistical Package Social Sciences (SPSS). Subsequently, there was a direct relationship recorded amongst DT, JS, and PM. In any case, university A scored marginally higher relationship amongst's DT, JS and PM when contrasted with other two public universities. As a conclusion, every public university has their own main goal and vision that should be accomplished. In this manner, distinctive systems may be utilized as a part of DT keeping in mind the end goal to get a decent association with JS and PM. In light of the discoveries acquired, it demonstrates that public universities have taken their own drive to help their JS and PM by utilizing DT has one of the methodologies, however, some way or another, the systems have taken still should be checked and re-organized to get the great connection between these two factors.